Fish biodiversity In the upstream of the Umban Sari River, Pekanbaru, Riau Province - Ricky R. Sihite; Efawani '; Deni Efizon (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The upstream the Umban Sari River was inhabit by numerous fish species. Information on these fish, however, is almost none. To understand the biodiversity of fish in that river, a study has been conducted from September to October 2015. The fish was sampled using several net types (mesh size 0.1 – 1.0 inch), electrofishing and scoop net. Data were then analyzed to find the relative profusion (Kr), fish occurrence frequency and the presence fish (Fi). The fish sampled were identified based on Kottelat (2013). Results shown that there were 15 species (8 families) present. There were Osteochilus hasselti, Parachela oxygastroides, Cyclocheilichthyes apogon, Esomus metallicus, Rasbora cephalotaenia, Rasbora trilineata, Clarias batrachus, Oreochromis niloticus, Channa striata , Trichogaster trichopterus, Trichogaster pectoralis, Trichopsis vittata, Pterygoplichthys pardalis , Xenentodon canciloides and Monopterus albus. The most common fish was Esomus metallicus. Trichogaster trichopterus and Channa striata were distributed evenly along the river, as they were found in each sampling area (Fi 100%). Besides the endemic fishes, there were 5 exotic species (Fi 37%) present, namely E. metallicus, O. niloticus, T. pectoralis, C. striata and P. pardalis.Keyword: fish biodiversity, Umban Sari River, Pekanbaru, Riau